LAMEMBA SEBAGAI LEMBAGA AKREDITASI MANDIRI: SEJARAH PERKEMBANGAN, KESIAPAN DAN TANTANGAN - Khalilah (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The authority to accreditate the study programs related with the field studies of economic, business, management and accounting was granted to Independent accreditation institution for economic, business, management and accounting study programs that is named as LAMEMBA, as imposed by National Accreditation Body for Higher Education’s regulation number 9/2020. This paper examines how this institution evolved and is being ready to do so and what challenges it encountered while managing to do so. Adopting a descriptive case study method, this paper reveals that this institution was established by Indonesian economic scholar association (ISEI), Indonesian accounting association (IAI) and Association of Indonesian Economic and Business Faculties (AFEBI) in 14 August 2019. Though being quite capable to serve as independent accreditation body to acreditate these aformentioned study programs, it encountered the following challenges: (1) total number of professional assessors is too small; (2) these assessors have had not enough time and resources to do so; and (3) most of these study programs are not fully capable to meet the minimum standard of accreditation.